Cyclodextrin and malto-dextrose collision cross sections determined in a drift tube ion mobility mass spectrometer using nitrogen bath gas. Issue 17 (1st August 2018) - Klein, Christian; Cologna, Stephanie M.; Kurulugama, Ruwan T.; Blank, Paul S.; Darland, Ed; Mordehai, Alex; Backlund, Peter S.; Yergey, Alfred L.
Abstract : Ion mobility measurements indicate unique distributions for cyclodextrin ions. Abstract : In this study, we have evaluated a low field limit drift tube ion mobility device for ion mobility-mass spectrometry (IM-MS) measurements that uses nitrogen as a bath gas with electrospray ionization on a modified Q-TOF instrument. We have determined reduced mobility ( K 0 ) and collision cross section (CCS) values for a group of analyte ions that have been characterized previously in other drift tube IM-MS instruments. Our determinations of CCS for this set of ions as well as for standards are in agreement with published values. Because of their importance in biophysics and pharmaceuticals, we expanded our analysis to investigate the properties of cyclodextrins in this system. We present CCS data for both positively and negatively charged cyclodextrins and, for purposes of comparison, maltodextrose ions. Our results are the first reports of these materials as negative ions.